Influência da fixação e de métodos de secagem na detecção de alterações proliferativas ultraestruturais induzidas pelo Diuron no urotélio vesical de ratos wistar - Fava, Rafaela Marono [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Diuron is a substituted urea herbicide, carcinogenic to the rat urinary bladder at high dietary levels (2500 ppm). Different scanning electron microscopy (SEM) processing methods resulted in differing observations of early urothelial changes induced by exposure to this herbicide. This study evaluated the influence of SEM processing methods on the detection of urothelial alterations induced by diuron. Male Wistar rats were divided into 3 groups: control (basal diet), 7.1% Sodium Saccharin (NaS) (positive control) and 2500 ppm diuron, and fed for 7 days or 15 weeks. Urinary bladders were fixed with Bouin’s or glutaraldehyde fixative and processed by critical point drying (CPD) or by hexamethyldisilazane (HMDS) for comparison of the cytotoxic and proliferative changes induced by diuron in the urothelium. Histological and cell proliferation evaluations were also performed. After seven days, no differences in the incidence of histological urothelial lesions or labeling indices were detected among the groups; however, the incidence of urothelial lesions after 15 weeks was significantly increased in the animals fed diuron or NaS. After seven days or 15 weeks, the severity of urothelial alterations was significantly higher in animals fed with diuron. Both fixative and drying methods allowed for the identification of prenecrotic swollen superficial cells in the urothelium after seven days exposure to 2500 ppm diuron. Our results confirmed that the presence of prenecrotic swollen cells in the urothelium is an early key event due to diuron cytotoxicity and is not an artifact related to the processing methods used
Keywords: Bexiga - Doenças; Diuron; Herbicidas; Microscopia eletronica de varredura; Bladder Diseases